If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-1=m/3=7
We move all terms to the left:
-1-(m/3)=0
We add all the numbers together, and all the variables
-(+m/3)-1=0
We get rid of parentheses
-m/3-1=0
We multiply all the terms by the denominator
-m-1*3=0
We add all the numbers together, and all the variables
-1m-3=0
We move all terms containing m to the left, all other terms to the right
-m=3
m=3/-1
m=-3
| M+7-n=4 | | 12y=4y-48 | | 71=3v+11 | | 2x=18−(4x+12) | | x-20=360 | | 7/2x+1/2x=17^1/2+9/2 | | 1.07x=15 | | -12=6x+19-9x | | 2x-80=100-4x | | 4d2=24 | | 5y+3(2y+1)=0 | | 7x-5+3x=6x+3+7-2x | | 9=3(6-2x) | | p+25=8 | | 4x+128=9x+126 | | (2x+5+(3x+10)=70 | | x5.58=5x-13.5-4x | | 14/15-x=620 | | X^/4x+3=0 | | 6x+12-10x=-10x | | 2x=2x+2=4x=2 | | 2=10-z/3 | | -4u-16=-2(u+9) | | 3x+24=3x+11 | | X^2/4x+3=0 | | 5/2x+1/2x=31/2x+7/2 | | w/2-8=-7 | | 5x+6=6x-16 | | −6x−15=4x+35 | | -4x+2+8=18 | | 4w+14=20 | | -(6x-18)=-12 |